Upaya Peningkatan Loyalitas melalui Brand Image, Brand Trust, dan Kepuasan sebagai Variabel Intervening: The Effort to Increase Loyalty through Brand Image, Brand Trust, and Satisfaction as Intervening Variables - Martin Martin; Nasib Nasib (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Polytechnic is a university focusing on vocational education. Politeknik Unggul LP3M is to provide an appropriate vocational education in supporting industrial demand. This study focuses on maximizing students’ loyalty influenced by brand image and trust, where students’ satisfaction is an intervening variable. Path analysis was chosen for this study. As many as 125 people were chosen as respondents, and the technique sampling used purposive random sampling. The study showed that brand image and trust significantly impact students’ loyalty and satisfaction in Politeknik Unggul LP3M. Students’ satisfaction has a crucial role in mediating brand image and brand trust on students’ loyalty.